Composite negative electrode material, preparation method thereof and sodium ion battery
Patent Information
- Application Number
- CN202311786243.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-22
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-12-22
AI Technical Summary
[0004]虽然上述策略可以提高材料的电化学性能,但目前的改进方案对于钠离子电池的稳定性改善效果不明显
[0051] This invention, by co-doping nitrogen and sulfur in the core of a hard carbon material, not only provides active sites and improves sodium storage capacity, but also increases interlayer spacing and specific capacity. In addition, the graphene coating not only provides a conductive network, improves conductivity and ion transport kinetics, and increases first-cycle coulombic efficiency, but also makes the coating more stable through amide bonding between the graphene layer and the core, which is beneficial to improving the long-term cycling stability of sodium ion storage.
Smart Images

Figure CN117727901B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery materials technology, specifically relating to a composite negative electrode material, its preparation method, and a sodium-ion battery. Background Technology
[0002] Hard carbon, due to its large lattice spacing, low potential, good stability, and disordered structure, exhibits high capacity and excellent cycle stability when used as a sodium-ion battery anode, making it the most promising candidate for commercialization. However, as the mainstream anode material for sodium-ion batteries, hard carbon suffers from fundamental problems such as low initial efficiency and low specific capacity. The root cause lies in the short-range ordered and long-range disordered structure of hard carbon, which creates a large potential barrier for sodium ion insertion, resulting in high ion migration impedance and unstable thermodynamic properties. Furthermore, the electronic state surrounding carbon atoms in hard carbon itself is unfavorable for sodium ion insertion, leading to poor kinetic performance.
[0003] In recent years, effective strategies for improving the electrochemical performance of hard carbon anodes have included atomic doping and coating. Atomic doping can not only increase the interlayer spacing, affecting electronic properties and creating a pseudocapacitive effect on the charge distribution of adjacent carbon atoms and electrolyte ions, but also benefit the coupling effect of power density and energy density in sodium-ion batteries. Heteroatom doping (such as N, S, or P) easily generates electrochemical defect sites, which is conducive to sodium ion adsorption. At the same time, the functionalization of the carbon material surface can improve the interaction between the electrode and the electrolyte. For example, nitrogen atoms are more likely to bond with carbon, and nitrogen doping can enhance conductivity, which is conducive to the sodium ion transport rate and improves kinetic performance; sulfur atom doping can introduce sodium storage active sites to increase specific capacity. The excellent electrochemical performance can be attributed to the open structure and the functionalized groups with high levels of atomic doping, as well as the defects generated, which can enhance sodium ion diffusion and provide more contact sites between the active material and the electrolyte. With the increasing market requirements for energy density and rate performance, one of the current methods to improve the energy density and rate of anode materials is surface coating, such as using soft carbon or hard carbon for coating.
[0004] While the above strategies can improve the electrochemical performance of materials, current improvement schemes have not significantly improved the stability of sodium-ion batteries.
[0005] Therefore, how to effectively improve the stability of hard carbon anode materials, thereby significantly improving the long-term stability of sodium-ion batteries during storage, is an urgent technical problem to be solved. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a composite anode material, its preparation method, and a sodium-ion battery. This invention, through nitrogen and sulfur co-doping in a hard carbon material core, not only provides active sites and improves sodium storage capacity but also increases interlayer spacing and specific capacity. Furthermore, the graphene coating not only provides a conductive network, improving conductivity and ion transport kinetics and enhancing first-cycle coulombic efficiency, but also, through amide bonding between the graphene layer and the core, makes the coating more stable, thus improving long-term cycling stability during sodium-ion storage.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a composite anode material comprising a nitrogen-sulfur co-doped hard carbon material core and a graphene layer covering the surface of the core, wherein the graphene layer and the core are connected by amide bonds.
[0009] This invention, by co-doping nitrogen and sulfur in the core of a hard carbon material, not only provides active sites and improves sodium storage capacity, but also increases interlayer spacing and specific capacity. In addition, the graphene coating not only provides a conductive network, improves conductivity and ion transport kinetics, and increases first-cycle coulombic efficiency, but also makes the coating more stable through amide bonding between the graphene layer and the core, which is beneficial to improving the long-term cycling stability of sodium ion storage.
[0010] As a preferred technical solution of the present invention, the particle size D50 of the nitrogen-sulfur co-doped hard carbon material core is 5-15 μm, for example, it can be 5 μm, 7 μm, 9 μm, 10 μm, 13 μm or 15 μm, etc.
[0011] Preferably, the thickness of the graphene layer is 1-5 nm, for example, it can be 1 nm, 2 nm, 3 nm, 4 nm or 5 nm.
[0012] As a preferred technical solution of the present invention, based on the mass of the nitrogen-sulfur co-doped hard carbon material core, the total doping amount of nitrogen and sulfur is 5-20%, for example, it can be 5%, 10%, 15% or 20%, etc.
[0013] In this invention, if the total doping amount of nitrogen and sulfur is too high, it will affect the synergistic relationship and reduce the first efficiency and cycle stability; if the total doping amount of nitrogen and sulfur is too low, the improvement effect will not be obvious and the capacity improvement will be low.
[0014] Preferably, in the nitrogen-sulfur co-doped hard carbon material core, the ratio of nitrogen to sulfur doping is (1-5):(1-2), wherein the nitrogen selection range "1-5" can be, for example, 1, 2, 3, 4 or 5, and the sulfur selection range "1-2" can be, for example, 1, 1.2, 1.4, 1.6, 1.8 or 2.
[0015] In this invention, if the ratio of nitrogen to sulfur doping is too small, i.e., the sulfur content is too large, the volume effect of sulfur atoms during sodium ion insertion / extraction will cause rapid capacity decay; if the ratio of nitrogen to sulfur doping is too large, i.e., the nitrogen content is too large, too many active sites will be introduced, which will cause excessive consumption of active lithium during the first SEI formation, increasing irreversible capacity and resulting in low first efficiency.
[0016] In a second aspect, the present invention provides a method for preparing the composite anode material as described in the first aspect, the method comprising the following steps:
[0017] (1) Mix hard carbon precursor and nitrogen-sulfur doping source, carry out hydrothermal reaction, and sinter to obtain nitrogen-sulfur co-doped hard carbon material.
[0018] (2) The nitrogen-sulfur co-doped hard carbon material is subjected to surface amino functionalization treatment to obtain amino functionalized products. Then, the amino functionalized products are mixed with graphene oxide dispersion and subjected to dehydration condensation reaction to obtain the composite anode material.
[0019] In this invention, a nitrogen-sulfur co-doped hard carbon material with a microsphere morphology is prepared by hydrothermal reaction of a hard carbon precursor and a nitrogen-sulfur doping source. Then, an atomic dopant with a stable chemical structure is formed by high-temperature sintering. After amino functionalization, it undergoes a dehydration condensation chemical bonding reaction with graphene oxide with carboxyl functional groups to form amide bonds and complete the carbon coating process.
[0020] In this invention, the hydrothermal method can simply, directly and effectively help materials form a spherical morphology, which is beneficial to their processing performance and compaction density.
[0021] As a preferred technical solution of the present invention, the hard carbon precursor in step (1) includes starch.
[0022] It should be noted that the present invention does not limit the type of starch. For example, it can be mung bean starch, tapioca starch, sweet potato starch, yam starch, potato starch, wheat starch, water chestnut starch, lotus root starch, or corn starch, etc.
[0023] Preferably, the nitrogen-sulfur doping source in step (1) includes a nitrogen-sulfur co-doped precursor.
[0024] Preferably, the nitrogen-sulfur co-doped precursor includes any one or a combination of at least two of thiourea, ammonium sulfide, or thioacetamide.
[0025] Preferably, the nitrogen-sulfur doping source in step (1) includes a nitrogen source and a sulfur source.
[0026] Preferably, the nitrogen source includes any one or a combination of at least two of ammonia, urea, melamine, polypyrrole, or ammonium bicarbonate.
[0027] Preferably, the sulfur source includes sulfur powder and / or sodium sulfide.
[0028] Preferably, the mass ratio of the hard carbon precursor and the nitrogen-sulfur doped source in step (1) is (3-10):1, for example, it can be 3:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1, etc.
[0029] As a preferred technical solution of the present invention, the temperature of the hydrothermal reaction in step (1) is 150-250℃, for example, it can be 150℃, 175℃, 200℃, 225℃ or 250℃, etc., and the time is 3-10h, for example, it can be 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h.
[0030] Preferably, the sintering in step (1) is carried out in an inert atmosphere.
[0031] Preferably, the gas in the inert atmosphere includes any one or a combination of at least two of nitrogen, argon, or helium.
[0032] Preferably, the gas flow rate in the inert atmosphere is 1-5 L / min, for example, it can be 1 L / min, 2 L / min, 3 L / min, 4 L / min or 5 L / min, etc.
[0033] Preferably, the sintering temperature in step (1) is 800-1500℃, for example, 800℃, 900℃, 1000℃, 1100℃, 1200℃, 1300℃, 1400℃ or 1500℃, and the time is 5-10h, for example, 5h, 6h, 7h, 8h, 9h or 10h.
[0034] In this invention, sintering is used to eliminate defects and impurities in biomass hard carbon, improve structural regularity, promote cross-linking density between molecular chains, and provide energy for the formation of chemical bonds between N, S, and C elements. If the sintering temperature is too low, it will result in more impurities, structural instability, and a lower first-efficiency; if the sintering temperature is too high, it will increase the degree of graphitization, reduce the interlayer spacing, hinder ion insertion / extraction, and decrease capacity.
[0035] Preferably, the heating rate of the sintering in step (1) is 1-10℃ / min, for example, it can be 1℃ / min, 3℃ / min, 5℃ / min, 7℃ / min or 9℃ / min, etc.
[0036] As a preferred technical solution of the present invention, the surface amino functionalization treatment step (2) includes:
[0037] Nitrogen-sulfur co-doped hard carbon materials and amino raw materials are mixed and reacted to obtain amino-functionalized products.
[0038] Preferably, the amino raw material includes ammonium fluoride and / or polyethyleneimine.
[0039] Preferably, the mass ratio of the nitrogen-sulfur co-doped hard carbon material to the amino raw material is (3-10):1, for example, it can be 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1, etc.
[0040] In this invention, the addition of amino raw materials is to introduce amino functional groups, forming them on the surface of the hard carbon material. These functional groups then bond with the carboxyl groups on the graphene oxide surface to complete the coating. If the mass ratio of nitrogen-sulfur co-doped hard carbon material to amino raw materials is too small, i.e., the amount of amino raw materials used is too large, the additional amino groups not adsorbed on the hard carbon surface will consume the subsequent graphene oxide functional groups, generating impurities and resulting in insufficient coating material. If the mass ratio of nitrogen-sulfur co-doped hard carbon material to amino raw materials is too large, i.e., the amount of amino raw materials used is too small, the introduction of functional groups will be insufficient, resulting in uneven coating, poor coating layer stability, and poor performance.
[0041] Preferably, the reaction temperature is 40-60℃, for example, 40℃, 45℃, 50℃, 55℃ or 60℃, and the time is 5-10h, for example, 5h, 6h, 7h, 8h, 9h or 10h.
[0042] As a preferred technical solution of the present invention, the mass ratio of the amino-functionalized product and the graphene oxide dispersion in step (2) is (10-100):1, for example, it can be 10:1, 30:1, 50:1, 70:1 or 90:1, etc.
[0043] Preferably, the temperature of the dehydration condensation reaction in step (2) is 25-40℃, for example, 25℃, 30℃, 35℃ or 40℃, and the time is 2-5h, for example, 2h, 2.5h, 3h, 3.5h, 4h or 4.5h.
[0044] As a preferred technical solution of the present invention, the preparation method includes the following steps:
[0045] (I) Mix starch and nitrogen-sulfur co-doped precursor at a mass ratio of (3-10):1, and carry out hydrothermal reaction at 150-250℃ for 3-10h. After drying the product, place it in an inert atmosphere and sinter at 800-1500℃ for 5-10h at a rate of 1-10℃ / min to obtain nitrogen-sulfur co-doped hard carbon material.
[0046] (II) The nitrogen-sulfur co-doped hard carbon material and ammonium fluoride solution are mixed at a mass ratio of (3-10):1 and stirred at 40-60℃ for 5-10 h to obtain amino-functionalized products;
[0047] (III) The amino-functionalized product and the graphene oxide dispersion are mixed at a mass ratio of (10-100):1 and subjected to a dehydration condensation reaction at 25-40°C for 2-5 hours to obtain the composite anode material.
[0048] Thirdly, the present invention provides a sodium-ion battery, wherein the negative electrode of the sodium-ion battery includes the composite negative electrode material as described in the first aspect.
[0049] The numerical range described in this invention includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] This invention, by co-doping nitrogen and sulfur in the core of a hard carbon material, not only provides active sites and improves sodium storage capacity, but also increases interlayer spacing and specific capacity. In addition, the graphene coating not only provides a conductive network, improves conductivity and ion transport kinetics, and increases first-cycle coulombic efficiency, but also makes the coating more stable through amide bonding between the graphene layer and the core, which is beneficial to improving the long-term cycling stability of sodium ion storage. Attached Figure Description
[0052] Figure 1 The graph shows the composite negative electrode material prepared in Example 1 of this invention after 500 charge-discharge cycles. Detailed Implementation
[0053] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0054] Example 1
[0055] This embodiment provides a composite anode material, which includes a nitrogen-sulfur co-doped hard carbon material core and a graphene layer covering the surface of the core. The graphene layer and the core are connected by amide bonds.
[0056] The particle size D50 of the nitrogen-sulfur co-doped hard carbon material core is 5 μm, the thickness of the graphene layer is 2 nm, and based on the mass of the nitrogen-sulfur co-doped hard carbon material core, the total doping amount of nitrogen and sulfur is 16%, and the doping ratio of nitrogen to sulfur is 2:1.
[0057] This embodiment also provides a method for preparing the above-mentioned composite anode material, the method comprising the following steps:
[0058] (1) 10g of corn starch and 2g of thiourea were added to 250mL of deionized water and mixed. After mixing evenly, the mixture was transferred to a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 180℃ for 5h. The resulting product was dried and transferred to a ceramic crucible and placed in an argon atmosphere with a flow rate of 3L / min. The temperature was increased to 1000℃ at a rate of 5℃ / min and sintered for 6h to obtain nitrogen-sulfur co-doped hard carbon material.
[0059] The mass ratio of corn starch to thiourea is 5:1.
[0060] (2) 10g of the nitrogen-sulfur co-doped hard carbon material was slowly added to 250mL of ammonium fluoride solution and stirred at 50°C for 6h to obtain the amino-functionalized product.
[0061] The mass ratio of nitrogen-sulfur co-doped hard carbon material to ammonium fluoride solution is 5:1.
[0062] (3) 100 mg and 100 mL of graphene oxide dispersion were titrated at a constant rate into 10 g and 100 mL of the amino-functionalized product, and a dehydration condensation reaction was carried out at 40 °C for 2 h to obtain the composite negative electrode material.
[0063] The mass ratio of the amino-functionalized product to the graphene oxide dispersion is 100:1.
[0064] Figure 1The graph shows the charge-discharge cycle performance of the composite anode material prepared in this embodiment after 500 cycles. As can be seen from the graph, this curve represents the charge-discharge curve of the composite material prepared in this embodiment after being assembled into a coin cell at 0-2V for the 500th cycle. Specifically, it is first discharged at a constant current rate of 0.05C to 0.01V, then discharged at a constant voltage and current limit to 0V, with a discharge capacity of 378mAh / g after 500 cycles; then it is charged at a constant current rate of 0.1C to 2V, with a charging capacity of 332mAh / g. The material still maintains a high capacity after 500 cycles, which is attributed to the capacity improvement brought by doping and the structural stability brought by coating.
[0065] Example 2
[0066] This embodiment provides a composite anode material, which includes a nitrogen-sulfur co-doped hard carbon material core and a graphene layer covering the surface of the core. The graphene layer and the core are connected by amide bonds.
[0067] The particle size D50 of the nitrogen-sulfur co-doped hard carbon material core is 10 μm, the thickness of the graphene layer is 3 nm, and based on the mass of the nitrogen-sulfur co-doped hard carbon material core, the total doping amount of nitrogen and sulfur is 9%, and the doping ratio of nitrogen to sulfur is 2:1.
[0068] This embodiment also provides a method for preparing the above-mentioned composite anode material, the method comprising the following steps:
[0069] (1) 10g of potato starch and 1g of thiourea were added to 500mL of deionized water and mixed. After mixing evenly, the mixture was transferred to a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 150℃ for 10h. The resulting product was dried and transferred to a ceramic crucible and placed in an argon atmosphere with a flow rate of 3L / min. The temperature was increased to 800℃ at a rate of 1℃ / min and sintered for 6h to obtain nitrogen-sulfur co-doped hard carbon material.
[0070] The mass ratio of potato starch to thiourea is 10:1.
[0071] (2) 10g of the nitrogen-sulfur co-doped hard carbon material was slowly added to 250mL of ammonium fluoride solution and stirred at 60℃ for 5h to obtain amino-functionalized product;
[0072] The mass ratio of nitrogen-sulfur co-doped hard carbon material to ammonium fluoride solution is 5:1.
[0073] (3) 100 mg and 100 mL of graphene oxide dispersion were titrated at a constant rate into 10 g and 100 mL of the amino-functionalized product, and a dehydration condensation reaction was carried out at 30 °C for 5 h to obtain the composite negative electrode material.
[0074] The mass ratio of the amino-functionalized product to the graphene oxide dispersion is 100:1.
[0075] Example 3
[0076] This embodiment provides a composite anode material, which includes a nitrogen-sulfur co-doped hard carbon material core and a graphene layer covering the surface of the core. The graphene layer and the core are connected by amide bonds.
[0077] The particle size D50 of the nitrogen-sulfur co-doped hard carbon material core is 5 μm, the thickness of the graphene layer is 5 nm, and based on the mass of the nitrogen-sulfur co-doped hard carbon material core, the total doping amount of nitrogen and sulfur is 17%, and the doping ratio of nitrogen to sulfur is 1:1.
[0078] This embodiment also provides a method for preparing the above-mentioned composite anode material, the method comprising the following steps:
[0079] (1) 10g corn starch, 1g ammonium bicarbonate and 1g sodium sulfide were added to 500mL of deionized water and mixed. After mixing evenly, the mixture was transferred to a polytetrafluoroethylene reactor and subjected to hydrothermal reaction at 200℃ for 5h. The resulting product was dried and transferred to a ceramic crucible and placed in an argon atmosphere with a flow rate of 3L / min. The temperature was increased to 1000℃ at a rate of 5℃ / min and sintered for 6h to obtain nitrogen-sulfur co-doped hard carbon material.
[0080] The mass ratio of corn starch to nitrogen and sulfur doping sources (ammonium bicarbonate and sodium sulfide) is 5:1.
[0081] (2) 10g of the nitrogen-sulfur co-doped hard carbon material was slowly added to 250mL of ammonium fluoride solution and stirred at 40°C for 10h to obtain the amino-functionalized product.
[0082] The mass ratio of nitrogen-sulfur co-doped hard carbon material to ammonium fluoride solution is 5:1.
[0083] (3) 100 mg and 100 mL of graphene oxide dispersion were titrated at a constant rate into 10 g and 100 mL of the amino-functionalized product, and a dehydration condensation reaction was carried out at 40 °C for 5 h to obtain the composite negative electrode material.
[0084] The mass ratio of the amino-functionalized product to the graphene oxide dispersion is 100:1.
[0085] Example 4
[0086] This embodiment provides a composite anode material, which includes a nitrogen-sulfur co-doped hard carbon material core and a graphene layer covering the surface of the core. The graphene layer and the core are connected by amide bonds.
[0087] The particle size D50 of the nitrogen-sulfur co-doped hard carbon material core is 5 μm, the thickness of the graphene layer is 5 nm, and based on the mass of the nitrogen-sulfur co-doped hard carbon material core, the total doping amount of nitrogen and sulfur is 23%, and the doping ratio of nitrogen to sulfur is 1:2.
[0088] This embodiment also provides a method for preparing the above-mentioned composite anode material, the method comprising the following steps:
[0089] (1) 10g corn starch, 2g ammonium bicarbonate and 1g sodium sulfide were added to 500mL deionized water and mixed. After mixing evenly, the mixture was transferred to a polytetrafluoroethylene reactor and subjected to hydrothermal reaction at 200℃ for 5h. The resulting product was dried and transferred to a ceramic crucible and placed in an argon atmosphere with a flow rate of 3L / min. The temperature was increased to 1000℃ at a rate of 5℃ / min and sintered for 6h to obtain nitrogen-sulfur co-doped hard carbon material.
[0090] The mass ratio of corn starch to nitrogen and sulfur doping sources (ammonium bicarbonate and sodium sulfide) is 10:3.
[0091] (2) 10g of the nitrogen-sulfur co-doped hard carbon material was slowly added to 250mL of ammonium fluoride solution and stirred at 40°C for 10h to obtain the amino-functionalized product.
[0092] The mass ratio of nitrogen-sulfur co-doped hard carbon material to ammonium fluoride solution is 5:1.
[0093] (3) 100 mg and 100 mL of graphene oxide dispersion were titrated at a constant rate into 10 g and 100 mL of the amino-functionalized product, and a dehydration condensation reaction was carried out at 40 °C for 5 h to obtain the composite negative electrode material.
[0094] The mass ratio of the amino-functionalized product to the graphene oxide dispersion is 100:1.
[0095] Example 5
[0096] The difference between this embodiment and embodiment 1 is that the ammonium fluoride solution in step (2) is replaced with a polyethyleneimine solution.
[0097] The remaining preparation methods and parameters are consistent with those in Example 1.
[0098] Example 6
[0099] The difference between this embodiment and embodiment 1 is that the amount of ammonium fluoride solution added in step (2) is adjusted so that the mass ratio of nitrogen-sulfur co-doped hard carbon material to ammonium fluoride solution is 10:1.
[0100] The remaining preparation methods and parameters are consistent with those in Example 1.
[0101] Example 7
[0102] The difference between this embodiment and embodiment 1 is that the amount of graphene oxide dispersion added in step (3) is adjusted so that the mass ratio of amino-functionalized product to graphene oxide dispersion is 10:1.
[0103] The remaining preparation methods and parameters are consistent with those in Example 1.
[0104] Example 8
[0105] The difference between this embodiment and embodiment 1 is that the sintering temperature in step (1) is adjusted to 1200℃.
[0106] The remaining preparation methods and parameters are consistent with those in Example 1.
[0107] Example 9
[0108] The difference between this embodiment and embodiment 1 is that the amount of thiourea added in step (1) is adjusted so that the total nitrogen and sulfur doping amount is 1%.
[0109] The remaining preparation methods and parameters are consistent with those in Example 1.
[0110] Example 10
[0111] The difference between this embodiment and embodiment 1 is that the amount of thiourea added in step (1) is adjusted so that the total nitrogen and sulfur doping amount is 25%.
[0112] The remaining preparation methods and parameters are consistent with those in Example 1.
[0113] Example 11
[0114] The difference between this embodiment and embodiment 3 is that the amount of sodium sulfide added in step (1) is adjusted so that the ratio of nitrogen to sulfur doping is 1:3.
[0115] The remaining preparation methods and parameters are consistent with those in Example 3.
[0116] Example 12
[0117] The difference between this embodiment and embodiment 3 is that the amount of sodium sulfide added in step (1) is adjusted so that the ratio of nitrogen to sulfur doping is 6:1.
[0118] The remaining preparation methods and parameters are consistent with those in Example 3.
[0119] Example 13
[0120] The difference between this embodiment and embodiment 1 is that the sintering temperature in step (1) is 700°C.
[0121] The remaining preparation methods and parameters are consistent with those in Example 1.
[0122] Example 14
[0123] The difference between this embodiment and embodiment 1 is that the sintering temperature in step (1) is 1600℃.
[0124] The remaining preparation methods and parameters are consistent with those in Example 1.
[0125] Example 15
[0126] The difference between this embodiment and embodiment 1 is that the mass ratio of nitrogen-sulfur co-doped hard carbon material to ammonium fluoride solution in step (2) is 2:1.
[0127] The remaining preparation methods and parameters are consistent with those in Example 1.
[0128] Example 16
[0129] The difference between this embodiment and embodiment 1 is that the mass ratio of nitrogen-sulfur co-doped hard carbon material to ammonium fluoride solution in step (2) is 12:1.
[0130] The remaining preparation methods and parameters are consistent with those in Example 1.
[0131] Comparative Example 1
[0132] The difference between this comparative example and Example 1 is that nitrogen and sulfur co-doping is not performed, that is, thiourea is not added in step (1).
[0133] The remaining preparation methods and parameters are consistent with those in Example 1.
[0134] Comparative Example 2
[0135] The difference between this comparative example and Example 1 is that step (3) is replaced by the following steps:
[0136] Weigh 100 mg of graphene powder and 10 g of amino-functionalized product and mix them by ball milling at 50 rpm for 5 h.
[0137] The remaining preparation methods and parameters are consistent with those in Example 1.
[0138] Performance testing
[0139] (i) The compaction density of the negative electrode materials prepared in the above embodiments and comparative examples is tested. The specific steps include: using a powder compaction tester, a commonly used laboratory testing instrument, to test the material with a pressure of 5T as the reference.
[0140] (ii) The negative electrode materials prepared in the above embodiments and comparative examples are made into negative electrode sheets and assembled to obtain sodium-ion batteries.
[0141] Battery assembly: Using the above-mentioned negative electrode material as the negative electrode, sodium metal sheet as the positive electrode, and 1.0 mol / L LiPF6 / EC (ethylene carbonate) + DMC (dimethyl carbonate) + FEC (fluoroethylene carbonate) (the volume ratio of EC, DMC and FEC is 4.5:4.5:1) as the electrolyte, CR2032 button batteries were assembled in an argon glove box.
[0142] The charge / discharge capacity, initial efficiency, and cycle performance of the above batteries were tested. The charge / discharge capacity and initial efficiency were tested using the LAND battery testing system at a voltage window of 0-2V and a current density of 100mA / g. The cycle performance test was performed on the button cell at a constant current charge / discharge density of 500mA / g, with a voltage range of 0-2V, and the capacity retention rate was obtained after 200 cycles.
[0143] The test results are shown in Table 1.
[0144] Table 1
[0145]
[0146]
[0147] analyze:
[0148] As shown in the table above, this invention forms a spherical material through a simple hydrothermal method, which is beneficial to its processing performance and compaction density. Nitrogen and sulfur co-doping in the core of the hard carbon material not only provides active sites and improves sodium storage capacity, but also increases the interlayer spacing and improves ion transport kinetics. At the same time, the graphene layer and the core are connected by amide bonding, which makes the coating more stable. It not only provides a conductive network to improve conductivity, but also introduces some functional groups to improve the first-cycle coulombic efficiency and capacity performance, demonstrating excellent cycling stability.
[0149] As shown in Examples 1 and 2, although the total nitrogen and sulfur doping amount decreased compared to Example 1, the compaction density did not change significantly. The doping elements can introduce active sites to provide sodium storage, so the subsequent electrochemical performance also showed a decrease in charge / discharge capacity. The first-cycle coulombic efficiency is largely related to the graphene coating, and therefore has little impact on the first-cycle efficiency.
[0150] As can be seen from Examples 1 and 3, although the capacity was improved by increasing the sulfur content in Example 3, the sulfide exhibited a certain volume expansion, which reduced the cycle stability.
[0151] As can be seen from Examples 1 and 4, the doping amount is higher than that of N element in Example 1, which introduces more defects, increases disorder, and increases specific surface area. Although it will also improve the first charge and discharge capacity, the formation of more SEI film causes more irreversible capacity, resulting in a lower first efficiency.
[0152] As can be seen from Examples 1 and 8, increasing the sintering temperature will significantly reduce material defects and oxygen-containing functional group content, reduce interlayer spacing, increase graphitization degree, which is not conducive to ion insertion / extraction and results in reduced capacity.
[0153] As can be seen from Examples 1 and 9-10, if the total doping amount of nitrogen and sulfur is too low, the effect of the doping element is not obvious and the capacity improvement is not obvious; if the total doping amount of nitrogen and sulfur is too high, the distinction between the host material and the doping element will be lost, affecting the synergistic relationship and reducing the first efficiency and cycle stability.
[0154] As can be seen from Examples 3 and 11-12, if the ratio of nitrogen to sulfur doping is too small, although the capacity will be improved, the volume effect generated by sulfur atoms during the ion insertion / extraction process will cause the capacity to decay rapidly; if the ratio of nitrogen to sulfur doping is too large, that is, the nitrogen content is too high, the introduction of too many active sites will cause more active lithium to be consumed during the first SEI generation, increasing the irreversible capacity and resulting in a low first efficiency.
[0155] As can be seen from Examples 1 and 13-14, if the sintering temperature is too low, there will be more impurities, unstable structure, and low first-time efficiency; if the sintering temperature is too high, the degree of graphitization will increase, the interlayer spacing will decrease, which is not conducive to ion insertion / extraction and reduces capacity.
[0156] As can be seen from Examples 1 and 15-16, if the mass ratio of nitrogen-sulfur co-doped hard carbon material to ammonium fluoride solution is too small, that is, if too much ammonium fluoride solution is used, additional substances will be introduced, resulting in an increase in the first irreversible capacity and a decrease in the first efficiency; if the mass ratio of nitrogen-sulfur co-doped hard carbon material to ammonium fluoride solution is too large, that is, if too little ammonium fluoride solution is used, the introduction of amino functional groups will be insufficient, resulting in incomplete coating and reduced cycle stability.
[0157] As can be seen from Example 1 and Comparative Example 1, the capacity will be significantly reduced if nitrogen and sulfur co-doping is not performed.
[0158] As can be seen from Example 1 and Comparative Example 2, if ball milling is used for coating, this method physically establishes the combination of the coating layer and the core. This physical coating method has poor coating uniformity and weak bonding force. However, Example 1 uses chemical bonding through dehydration condensation, which results in strong coating uniformity and better long-term cycling stability.
[0159] The applicant declares that the present invention is illustrated by the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a composite negative electrode material, characterized in that, The composite anode material includes a nitrogen-sulfur co-doped hard carbon material core and a graphene layer covering the surface of the core, wherein the graphene layer and the core are connected by amide bonds. The preparation method includes the following steps: (1) A hard carbon precursor and a nitrogen-sulfur doping source are mixed and subjected to a hydrothermal reaction. After sintering, a nitrogen-sulfur co-doped hard carbon material is obtained. The hard carbon precursor includes starch. The nitrogen-sulfur doping source includes a nitrogen-sulfur co-doped precursor and / or includes a nitrogen source and a sulfur source. The nitrogen-sulfur co-doped precursor is selected from any one or at least two of thiourea, ammonium sulfide or thioacetamide. The nitrogen source is selected from any one or at least two of ammonia, urea, melamine, polypyrrole or ammonium bicarbonate. The sulfur source is selected from sulfur powder and / or sodium sulfide. The mass ratio of the hard carbon precursor and the nitrogen-sulfur doping source in step (1) is (3-10):
1. (2) The nitrogen-sulfur co-doped hard carbon material is subjected to surface amino functionalization treatment to obtain amino functionalized products. Then, the amino functionalized products are mixed with graphene oxide dispersion and subjected to dehydration condensation reaction to obtain the composite negative electrode material.
2. The preparation method according to claim 1, characterized in that, The particle size D50 of the nitrogen-sulfur co-doped hard carbon material core is 5-15 μm.
3. The preparation method according to claim 1, characterized in that, The thickness of the graphene layer is 1-5 nm.
4. The preparation method according to claim 1, characterized in that, Based on the mass of the nitrogen-sulfur co-doped hard carbon material core, the total doping amount of nitrogen and sulfur is 5-20%.
5. The preparation method according to claim 1, characterized in that, In the nitrogen-sulfur co-doped hard carbon material core, the ratio of nitrogen to sulfur doping is (1-5):(1-2).
6. The preparation method according to claim 1, characterized in that, The hydrothermal reaction in step (1) is carried out at a temperature of 150-250℃ for 3-10 hours.
7. The preparation method according to claim 1, characterized in that, The sintering in step (1) is carried out in an inert atmosphere.
8. The preparation method according to claim 7, characterized in that, The gas flow rate in the inert atmosphere is 1-5 L / min.
9. The preparation method according to claim 1, characterized in that, The sintering temperature in step (1) is 800-1500℃ and the time is 5-10h.
10. The preparation method according to claim 1, characterized in that, The heating rate for sintering in step (1) is 1-10℃ / min.
11. The preparation method according to claim 1, characterized in that, Step (2) of the surface amino functionalization treatment includes: Nitrogen-sulfur co-doped hard carbon materials and amino raw materials are mixed and reacted to obtain amino-functionalized products.
12. The preparation method according to claim 11, characterized in that, The amino raw materials include ammonium fluoride and / or polyethyleneimine.
13. The preparation method according to claim 11, characterized in that, The mass ratio of the nitrogen-sulfur co-doped hard carbon material to the amino raw material is (3-10):
1.
14. The preparation method according to claim 11, characterized in that, The reaction is carried out at a temperature of 40-60℃ for 5-10 hours.
15. The preparation method according to claim 1, characterized in that, The mass ratio of the amino-functionalized product to the graphene oxide dispersion in step (2) is (10-100):
1.
16. The preparation method according to claim 1, characterized in that, The temperature of the dehydration condensation reaction in step (2) is 25-40℃ and the time is 2-5h.
17. The preparation method according to claim 1, characterized in that, The preparation method includes the following steps: (I) Mix starch and nitrogen-sulfur co-doped precursor at a mass ratio of (3-10):1, and carry out hydrothermal reaction at 150-250℃ for 3-10h. After drying the product, place it in an inert atmosphere and sinter at 800-1500℃ for 5-10h at a rate of 1-10℃ / min to obtain nitrogen-sulfur co-doped hard carbon material. (II) The nitrogen-sulfur co-doped hard carbon material and ammonium fluoride solution are mixed at a mass ratio of (3-10):1 and stirred at 40-60℃ for 5-10 h to obtain amino-functionalized products; (III) The amino-functionalized product and the graphene oxide dispersion are mixed at a mass ratio of (10-100):1 and subjected to a dehydration condensation reaction at 25-40°C for 2-5 hours to obtain the composite anode material.
18. A sodium-ion battery, characterized in that, The negative electrode of the sodium-ion battery includes a composite negative electrode material prepared by the preparation method according to any one of claims 1-17.
Citation Information
Patent Citations
Molybdenum disulfide(at)graphdiyne composite material, preparation method and application
CN113299893A
Phosphorus-iron co-doped hard carbon composite material as well as preparation method and application thereof
CN115513434A